MORBIDITY AND MORTALITY FROM MALIGNANT NEOPLASMS ASSOCIATED WITH HUMAN PAPILLOMAVIRUS - O. P. Gretsova; A. A. Kostin; Yu. V. Samsonov; G. V. Petrova; M. Yu. Prostov; Yu. I. Prostov (Исследования и практика в медицине)
In this review we continue the publication of data on the problem of malignant neoplasms (MN) associated with human papillomavirus (HPV), in Russia. In a previous publication (Research’n Practical Medicine Journal 2016; 3(1): 66–78. DOI: 10.17709/2409-2231-2016-3-1-9) we at the first time presented the data on the incidence of malignant tumors associated with HPV in the Russian Federation for the period from 2009 to 2014. This article presents updated data on the incidence of in 2015, as well as data on mortality from the MN associated with HPV in Russia with the analysis of trends in men and women in different age groups. The statistics used in the article is calculated according to the annual state reporting documentation of the statistical form of the Ministry of health No. 7 and No. 35, forms 5 and Rosstat data, the combined database of the state of the cancer register of the Russian Federation.